Применение ускоренных электронов в неразрушающем контроле - Каратаев В. Д. Владимир Дмитриевич; Кононов Б. А. Борис Александрович; Руденко В. Н.; Сорокин В. Б. Владимир Борисович (Дефектоскопия, 1979)
В фонде НТБ ТПУ отсутствует